Embryo-Specific Gene Expression in Microspore-Derived Embryos of Brassica napus. An Interaction between Abscisic Acid and Jasmonic Acid, - Hays, Dirk B. (American Society of Plant Physiologists, 1999)
The induction of napin and oleosin gene expression in Brassica napus microspore-derived embryos (MDEs) was studied to assess the possible interaction between abscisic acid (ABA) and jasmonic acid (JA). Napin and oleosin transcripts were detected sooner following treatment with ABA than JA. Treatment of MDEs with ABA plus JA gave an additive accumulation of both napin and oleosin mRNA, the absolute amount being dependent on the concentration of each hormone. Endogenous ABA levels were reduced by 10-fold after treatment with JA, negating the possibility that the observed additive interaction was due to JA-induced ABA biosynthesis. Also, JA did not significantly increase the uptake of [(3)H-ABA] from the medium into MDEs. This suggests that the additive interaction was not due to an enhanced carrier-mediated ABA uptake by JA. Finally, when JA was added to MDEs that had been treated with the ABA biosynthesis inhibitor fluridone, napin mRNA did not increase. Based on these results with the MDE system, it is possible that embryos of B. napus use endogenous JA to modulate ABA effects on expression of both napin and oleosin. In addition, JA could play a causal role in the reduction of ABA that occurs during late stages of seed development.